Phase transition and equation of state of paratellurite (TeO2) under high pressure. (18th July 2016) - Liu, Xun; Mashimo, Tsutomu; Kawai, Nobuaki; Sekine, Toshimori; Zeng, Zhaoyi; Zhou, Xianming
Abstract: The Hugoniot data for TeO2 single crystals were obtained for pressures up to ∼85 GPa along both the 〈100〉 ( a -axis) and 〈001〉 ( c -axis) directions using a velocity interferometer system for any reflector and inclined-mirror method combined with a powder gun or two-stage light gas gun. The Hugoniot-elastic limit of TeO2 was determined to be 3.3–4.3 GPa along the c -axes. The shock velocity ( U s ) versus particle velocity ( U p ) relation for TeO2 shows a kink around U p = 1.0 km s −1, which suggests a phase transition completes at ∼26 ± 2 GPa. The Hugoniot relations of the low and high pressure phase are given by U s = 3.13(5) + 1.10(6) U p for U p < 1.0 km s −1 and U s = 2.73(9) + 1.49(5) U p for U p > 1.0 km s −1, respectively. First-principles geometry optimizations based on the generalized gradient approximation after Perdew, Burke and Ernzerhof method were also performed on TeO2 . It suggested that a continuous structure distortion occurs up to 22 GPa, and the lattice parameters b and c abruptly increase and decrease at 22 GPa, respectively, indicating a first - order phase transition to the cotunnite structure phase. The equation of state of the cotunnite phase TeO2 is discussed based on the experimental and simulation results.